The Implementation of Digital Marketing at Diniyyah Al-Azhar Islamic Boarding School Foundation, Jambi, Indonesia - Abdul Muhaimin Elyusufi; Triyono Adi Tristanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Yayasan Pondok Pesantren Diniyyah (YPPD) Al-Azhar Jambi is an Islamic foundation that works in the field of education. Foundation operates education as formal school with various educational levels starting from Kindergarten up to higher institution which specializes in Teacher Training and Education, and Religious College (Tarbiyah) and Sciences. School which is under management of YPPD Al-Azhar Jambi, is one of favorite quality schools in Jambi province. In order to keep up with the times and the dynamic development of world education, promotion and marketing of YPPD Al-Azhar Jambi is carried out by conventional and online marketing, namely Digital Marketing. The presence of online technology such as Digital Marketing is indeed a significant contribution in the world of education. This research is about the implementation of Digital Marketing at YPPD Al-Azhar Jambi, Indonesia. The purpose of the study was to provide insightful contribution to YPPD Al-Azhar Jambi in order to grow and develop. The method used for this qualitative study is data analysis, observation and SWOT analysis. The results showed that the application of Digital Marketing at YPPD Al-Azhar Jambi had not been carried out optimally. YPPD Al-Azhar Jambi is suggested to manage and develop integrated marketing plans and strategies digitally.